THE EFFECT OF QUIZIZZ ON ENGLISH ACHIEVEMENT OF TENTH GRADE EFL STUDENTS - Ni Putu Titanisya Aurena Lawnsky (Language and Education Journal Undiksha, 2022)
This study aimed to investigate the effect of Quizizz application on SMA Negeri 1 Singaraja's tenth-grade students' English achievement. This study was a quasi-experimental study utilizing a post-test-only control group design. This study’s population was all tenth-grade students of SMA Negeri 1 Singaraja in the academic year 2020/2021, which consisted of 366 students. Cluster random sampling was used as a sampling technique for this study. There were two classes used as the sample of this study, namely X MIPA 4 and X MIPA 6. The two classes used as a sample consisted of 34 students, respectively. Class X MIPA 4 was used as an experimental group taught using Quizizz. In contrast, X MIPA 6 was used as a control group taught without Quizizz. The data collection method in this study used a multiple-choice test which consisted of 19 questions. The English test covered three topics: simple past and present perfect tense, recount text, and narrative text. The data obtained showed the value of the experimental group (M = 84.51, p-value = 0.012) and the control group (M = 78.16, p-value = 0.012). Based on the data obtained, it was known that the average value of the experimental group was greater than the control group. Furthermore, it was also known that the significance value obtained 0.012, which was less than 0.05. Comparing the mean value of the control and experimental groups, which is supported by the significance value, proves that Quizizz affects students’ English achievement.